RESEARCH-BASED DISASTER MITIGATION EDUCATION BASED ON THE NUSA TENGGARA CASE STUDY - Luthfin, Ahmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Indonesia is an archipelagic country located in the Pacific ring of fire, making the Indonesian nation has many islands and is prone to earthquakes. One of the islands in Indonesia is the Nusa Tenggara archipelago. It has a Back Arch Trust due to pressure under the Australian continent, resulting in the Nusa Tenggara region being prone to earthquakes. Administratively, Nusa Tenggara comprises the Provinces of West Nusa Tenggara and East Nusa Tenggara. This research aims to analyze an area on the island of Nusa Tenggara related to its vulnerability to earthquake disasters. The method is carried out by analyzing literature studies to obtain the distribution of disasters and determine the Mitigation suggestions to be determined. Based on research results from academics who have published journals as a reference for determining policies in disaster mitigation. Based on the research and literature studies, it can be concluded that the Nusa Tenggara area is prone to earthquakes.For this reason, mitigation activities in the Nusa Tenggara Islands must be carried out continuously and sustainably so that the community understands related to Disaster Mitigation as a whole. As for the Mitigation that we suggest, it is necessary to socialize the Map of earthquake-prone areas to be used as a reference for development, Construction of earthquake-resistant houses, good cooperation between researchers and the government in the socialization of Mitigation, Using lightweight and shock-resistant building materials, mitigation education that is integrated with the curriculum in the Nusa Tenggara region.